Humor and Gen- Z: A Reception Study of Bintang Emon's Stand-Up Comedy in Somasi Content - Yulius Kurniadi; Mujiono Mujiono; Silvanus Alvin (Dinasti International Journal of Education Management And Social Science, 2023)
Amidst the global pandemic, stand-up comedy in Indonesia experienced rapid growth as comedians turned to digital platforms, particularly YouTube, to entertain a broader audience confined to their homes. This shift allowed them to connect with fans and cater to the increasing demand for entertainment during uncertain times. The study focuses on analyzing the reception of Bintang Emon's stand-up comedy video from the Somasi event. Bintang's use of satire, sarcasm, and irony resonated with Generation Z, the target audience, as he touched on various societal issues and political events. The reception analysis revealed dominant, oppositional, and negotiation stances among the audience, reflecting diverse perspectives within this demographic. Understanding the preferences and perspectives of Generation Z can guide comedians in crafting relevant and engaging content, maintaining audience interest, and contributing to a more informed and connected society. This research sheds light on the effectiveness and impact of stand-up comedy performances, showcasing their role as a means of social commentary in addressing timely and relatable topics, thus providing valuable insights into public sentiment and attitudes.